Awareness of medical students on Human rabies and its prevention – A Study conducted in PRM Medical College, Baripada, Odisha (Journal of Pharmaceutical Negative Results, 2023)
Background - Rabies is an acute highly fatal communicable disease. Most of the death occurs due to lack of awareness about the urgency of local wound treatment & vaccination of the animal bite cases.Objective of the study -To asses the knowledge of medical students regarding the human rabies.To asses the knowledge on post-exposure prophylaxis for prevention of rabies.Study Design - Cross-sectional study.Place of study - PRM Medical College, Baripada, Mayurbhanj, Odisha.Study Subject - All the MBBS students of Phase - III Part-1 & Part-2 students of 2021 Batch.Study Instrument - A per-designed pretested questionnaires.Data analysis - It was analyzed with MS Excel.Result - Out of 157 study subjects all the students 100% know the disease Rabies and 96.82% know the causation agent of Rabies. Almost 86% had knowledge regarding the animals transmits the disease virus. About 96% subjects had knowledge of wound washing after animal bite.Around 97% had knowledge of post-exposure prophylaxis. 76% were aware of availability of various types of Vaccines & 74.5% had correct knowledge of vaccine regimen. 45% had answered correctly about the IM dose & 56% ID dose. Almost 92% had correct knowledge about dose of ERIG & 87% had HRIG. Only 78% had knowledge about per-exposure prophylaxis.ilonidal sinus over sacrococcygeal area is an acquired condition which affects young male adults usually. We did a retrospective chart review in the department of general surgery ,Kalinga Institute of Medical Sciences ,Bhubaneswar, for patients who underwent limberg flap repair for pilonidal sinus from sept 2015 to sept 2021 (6 years and 8 months) .A total of 49 patients with 40 males and 9 females respectively, were operated and they had a minimal post operative pain ,average post operative hospital stay of 6 days and early return to work in 3 weeks. Four out of 49 patients developed seroma ,out of which 1 was lost to follow up .Remaining 3 took two weeks to heal with regular dressings and no recurrence so far .One patient developed stitch granuloma and was treated conservatively. Hence Limberg flap for sacrococcygeal pilonidal sinus was found to be very useful in terms of post operative pain ,infection rate,patient compliance ,early return to work and almost nil recurrence rates.